2016
DOI: 10.2147/cia.s104618
|View full text |Cite
|
Sign up to set email alerts
|

Person-centered dementia care: current perspectives

Abstract: Person-centered dementia care is widely accepted as a value-based commitment to supporting people with dementia and is a guiding principle in care services. Policy ambitions to put people at the center of their own care are being developed internationally. These may be seen as part of the evolution of person-centered care which has its origins in critical perspectives on practice and social responses to people with dementia. In England, one further development of person-centered care has been personalization –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 25 publications
(26 reference statements)
1
59
0
7
Order By: Relevance
“…Person‐centredness is described by McCormack & McCance () as living one's own life while doing meaningful activities despite symptoms of dementia. Further, Edvardsson et al () described person‐centredness in the caring context, person‐centred care, which is commonly seen as a standard for high‐quality care, especially in the care of persons with dementia (Manthorpe & Samsi, ; Ruggiano & Edvardsson, ). It is possible for persons with dementia to be cared for by their spouses in a unique person‐centred way because of their life experience together in a manner that only they could achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Person‐centredness is described by McCormack & McCance () as living one's own life while doing meaningful activities despite symptoms of dementia. Further, Edvardsson et al () described person‐centredness in the caring context, person‐centred care, which is commonly seen as a standard for high‐quality care, especially in the care of persons with dementia (Manthorpe & Samsi, ; Ruggiano & Edvardsson, ). It is possible for persons with dementia to be cared for by their spouses in a unique person‐centred way because of their life experience together in a manner that only they could achieve.…”
Section: Discussionmentioning
confidence: 99%
“…In response to growing worldwide demand for health and social care, policy makers and service providers are the developing strategies and interventions that reflect their capacity and resources, and align with their country's public health principles, priorities and culture (Manthorpe & Samsi, ; World Health Organization, ). The standard and availability of support to people with dementia has a direct influence on their independence, health and well‐being, which, in turn, determine their quality of life (Eggenberger, Heimerl, & Bennett, ; Hallberg et al, ; Rothera et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A person‐centred framework is accepted widely as the gold standard in this regard (Downs & Collins, ; Love & Pinkowitz, ). Commonly associated with the work of Kitwood and Bredin (), the principles of person‐centred care recognise that each person with dementia has an enduring sense of self that comprises their individual feelings, thoughts and preferences (Manthorpe & Samsi, ). Fundamental to person‐centred care are effective verbal and non‐verbal communication, developing rapport, and being focused on the person, rather than completing a task (Hansen et al, ; Livingston et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This implies, among other things, supporting the physical and mental health of persons suffering from dementia, and the facilitation of coping, belonging, and experience of meaningfulness. Person-centred care is highly emphasized, 10,11 and environmental treatments, such as song and music therapy, are described as a central approach. Studies have shown that implementing song and music therapy in dementia care has positive impacts, and familiar and preferred music is found to increase the sense of environmental familiarity for people suffering from dementia.…”
Section: Introductionmentioning
confidence: 99%